COMPARISON ANALYSIS OF CAMEL RATIO BETWEEN BANK MANDIRI AND BANK NEGARA INDONESIA PERIOD 2008-2012 - Tuna, Vivid Virginia (FEB Universitas Sam Ratulangi Manado, 2013)
The banking sector has a huge potential and opportunities in its role as a source of financing for the public and business sectors. Since many banks are liquidated when the monetary crisis, Bank Indonesia made more incentive to restructure the banking system is expected to bring wrong banking structure, effective, efficient and healthy. Soundness of bank can be assessed to the qualitative approcah to the management factors and quantitative approach to the factors of capital, asset quality, management, earnings and liquidity. Known as CAMEL Analysis Ratio. This aim of this research is to know the level of health of Bank Mandiri and Bank Negara Indonesia from 2008 to 2012. The benefits of this research is increasing the financial performance of Bank Mandiri and Bank Negara Indonesia and the data can be used for the furthur information. This research is used CAMEL (Capital, asset quality, management, earning and liquidity) Ratio Analysis to assess the bank soundness. CAR ratio has no significant effect on problematic conditions and positive effect means that higher the CAR, the possibility of banks in the less troubled conditions In the CAR, KAP, NIM, ROA, BOPO and LDR show that just a very small nominal in comparing the both banks. Generally, Bank Mandiri has a bit bigger nominal about the CAR, KAP, NIM, ROA, BOPO and LDR between Bank Negara Indonesia. The question in the research problem is: Are there any differences of bank soundess between Bank Mandiri and Bank Negara Indonesia period 2008-2012 using CAMEL ratio?. The answer is very clearly as what that already explain above which is there is no significant difference about bank soundness between Bank Mandiri and Bank Negara Indonesia period 2008-2012 from the manual test and the statistical test. Keyword: CAMEL ratio, bank soundness